A novel mutation in USF1 gene is associated with familial combined hyperlipidemia. Issue 4 (14th November 2019) - Taghizadeh, Eskandar; Mirzaei, Farzaneh; Jalilian, Nazanin; Ghayour Mobarhan, Majid; Ferns, Gordon A.; Pasdar, Alireza
Abstract: Background: Familial combined hyperlipidemia or FCHL is one of the most common genetic causes of hyperlipidemia and is associated with elevation of cholesterol, triglycerides or both, and increased serum apolipoprotein B (apoB). Linkage analysis and next generation sequencing have been successfully used for identifying rare genetic variants that have moderate‐to‐large effects. Methods: We characterized a large pedigree from a proband identified following recruitment into the MASHAD study, in northeast Iran, with FCHL accompanied by early‐onset coronary artery disease. We used linkage analysis for several candidate regions in previous studies such as 1q21‐23, 11q23, and 8p, and then whole‐exome sequencing to identify the disease‐associated gene in this family. Results: We identified a novel variant in the USF1 gene, leading to a substitution of a tryptophan for arginine at position 196. Arg196Trp co‐segregated in all the affected family members in this pedigree with clinical syndrome and was not found in any unaffected family members of this pedigree, or in unrelated controls. Conclusions: We speculate that this mutation [Arg196Trp] in the USF1 gene might be associated with FCHL and early‐onset coronary heart disease in this family. However, the substantial mechanism requires further investigation. These findings indicate that USF1 plays an important role in the biological pathways associated with lipid metabolism.